2016
DOI: 10.5937/industrija1-10466
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable urban development and industrial pollution

Abstract: Sustainable development of cities is highly connected with the pollution generated from industrial facilities and power plants. Both affect quality of air, weather, health and quality of life. The main goal of this paper is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Newly built facilities occupy a large percentage of construction land, which results in a reduction of areas under the greenery, which is an additional problem. Traffic is one of the significant air pollutants in Novi Sad, in addition to the exhaust gases from industrial plants and thermal heating plants (Petrović et al, 2016). One of the adequate solutions to traffic jams is to use bicycles as much as possible.…”
Section: Problems Caused By the Urban Changesmentioning
confidence: 99%
“…Newly built facilities occupy a large percentage of construction land, which results in a reduction of areas under the greenery, which is an additional problem. Traffic is one of the significant air pollutants in Novi Sad, in addition to the exhaust gases from industrial plants and thermal heating plants (Petrović et al, 2016). One of the adequate solutions to traffic jams is to use bicycles as much as possible.…”
Section: Problems Caused By the Urban Changesmentioning
confidence: 99%
“…Many studies have shown that beside industry, district thermal power plants have huge responsibility for causing air pollution (He, Ye & Zhao, 2013;Wissner, 2014;Zanobetti & Petres, 2015;Nikolić, 2015;Petrović et al, 2016). In fact, almost all of the district thermal power plants use fossil fuels that produce high concentration of hazardous gases due to oil combustion during the production process.…”
Section: Environmental Effects In Price Liberalized Heating Sector Ofmentioning
confidence: 99%
“…As humans that are exposed to air pollution, water pollution and soil pollution among others, we also face an increased risk of falling victim to illness and disease. Industries may be significant contributors to air pollution experienced by local populations (Mohd Noor et al, 2018;Petrovic et al, 2016). There are many studies have inestigated the possible contribution to poor air quality accounted for 4.5 million premature death worldwide and 5% of those diagnosed with lung cancer will be due to extended exposure to pollution.…”
Section: Introductionmentioning
confidence: 99%